Time to First Line Antiretroviral Therapy Adverse Drug Reaction and its Predictors Among Adult HIV/AIDS Patients on Treatment in Eastern Ethiopia - Weldesenbet, Adisu Birhanu; Tusa, Biruk Shalmeno; Debele, Gebiso Roba; Sisay, Malede Mequanent; Ayele, Tadesse Awoke (Frontiers in Pharmacology, 2022)
Background: Even though determining the time to Anti-Retroviral Therapy Adverse Drug Reaction (ART ADR) and its predictors is a crucial step to overcome the negative consequences of the ADR, there is limited information regarding time to ART ADR and its predictors. Therefore, this study aimed to determine time to first ART ADR and its predictors among adult HIV/AIDS patients on first line antiretroviral therapy in West Hararghe zone, Eastern Ethiopia. Methods: An institution-based retrospective cohort study was conducted on 561 HIV/AIDS patients on first line ART from September 2013 to January 2019 at public hospitals in West Hararghe zone, Eastern Ethiopia. Data were collected using checklist and document review, entered using Epi-info and analyzed in R software. Cox proportional hazard model was fitted to identify predictors of time to first ART ADR. Model adequacy was checked using cox Snell residuals. Adjusted hazard ratio with its confidence interval was used to show presence and strength of association at 95% confidence level. Result: Most (90.74%) of ART ADRs occurred within one year of initiation of ART. Overall, 54 patients developed ART ADR with incidence density of 3.50/100 persons-years of observations (95% CI: 2.67 - 4.58). Initial ART regimen (TDF, 3TC, EFV) [AHR=0.27, 95%CI 0.11-0.67], fair adherence [AHR=8.77, 95%CI 3.31-23.24], poor adherence [AHR=7.84, 95% CI 3.15-19.51], moderate body mass index (BMI) at baseline [AHR=4.43, 95%CI 1.78-11.01], severe body mass index [AHR=2.79, 95%CI 1.15-6.77], world health organization (WHO) stage II [AHR=3.70, 95%CI 1.22-11.26] and WHO stage IV [AHR=6.32, 95%CI 2.01-19.85] were significant predictors of time to ART ADR. Conclusion: In conclusion most of the ART ADRs occurred in the within one year of initiation of ART. Initial ART regimen (TDF, 3TC, EFV), adherence, HIV/AIDS stage, and BMI were risk factors for time to ART ADR. Incidence of antiretroviral therapy adverse reaction was relatively low with early onset. Close monitoring for clients in clinical stage II and above is needed and continuous assessment for improving detection and management of ADRs is recommended. Patients with poor adherence need to get continuous counseling to improve their adherence status.